Implementasi Penilaian Kinerja Guru Melalui Supervisi Pembelajaran - Mujahidin Mujahidin; Solechan Solechan; Zahrotun Ni’mah Afif; Astri Liani (At Tadbir: Islamic Education Management Journal, 2025)
This study aims to explore the implementation of learning supervision at MTs Miftahul Ulum Cermenan Jombang, as well as supporting and inhibiting factors in teacher performance assessment. This study uses a qualitative approach with in-depth interviews as a method of data collection, involving the principal, supervision team, and several teachers at the school. The results of the study indicate that the implementation of supervision at MTs Miftahul Ulum is carried out in a structured manner twice a year, with the main focus on Teacher Performance Assessment (PKG) in the even semester. Supervision is carried out using two techniques, namely direct supervision through classroom observation and indirect supervision through meetings and group discussions between teachers. The main supporting factors are teacher mastery of technology, a conducive school culture, adequate facilities and infrastructure, and the existence of a competent supervision team. However, there are several inhibiting factors, such as time constraints, schedule clashes with other activities, and challenges in the readiness of learning devices and student discipline problems. The implications of this study indicate the need to develop a more flexible and data-based supervision system and improve teacher skills in utilizing technology to support the quality of learning. The results of this study can be used as consideration in developing supervision policies and practices in other schools, especially in utilizing technology to improve the effectiveness of supervision and the quality of learning